From temple to church : destruction and renewal of local cultic topography in late antiquity - Hahn, Johannes, 1957-; Emmel, Stephen.; Gotter, Ulrich. (Religions in the Graeco-Roman World, 2008)
Destruction of temples and their transformation into churches are central symbols of late antique change in religious environment, socio-political system, and public perception. Contemporaries were aware of these events' far-reaching symbolic significance and of their immediate impact as demonstrations of political power and religious conviction. Joined in any "temple-destruction" are the meaning of the monument, actions taken, and subsequent literary discourse. Paradigms of perception, specific interests, and forms of expression of quite various protagonists clashed. Archaeologists, historians, and historians of religion illuminate "temple-destruction" from different perspectives, analysing local configurations within larger contexts, both regional and imperial, in order to find an appropriate larger perspective on this phenomenon within the late antique movement "from temple to church".